Experimenatal study of pre-strain on the shape memory effect in ethylene vinyl acetate (EVA), polystrene(PS) & polymethyl methacrylate(PMMA) - Peh, Khian Huat. (2013)
Shape memory polymers have the ability to recover to its original shape even when its physical appearance undergoes significant and seemingly plastic deformation (i.e. Indention Mark) with the presence of the right stimulus such as heat (Thermo-responsive) and etc.